Southern House Spider, Kukulcania (= Filistata) hibernalis Hentz (Arachnida: Arneae: Filistatidae) - Glavis B. Edwards; K. McCanless (EDIS)
The southern house spider, Kukulcania (Filistata) hibernalis Hentz, is a conspicuous arachnid in Florida due to its relatively large size and distinctive flat, tangled web. It is common throughout Florida and much of the southern United States in human populated areas. Males of this species are often mistaken for the notorious brown recluse spider, Loxosceles reclusa Gertsch and Mulaik, because of their color and general shape. Southern house spiders are not known to have a dangerous bite. However, two bite cases reportedly caused the victims pain and swelling for a few days. This document is EENY-144, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: July 2000. Revised: June 2003.